The clean development mechanism and the international diffusion of technologies: An empirical study - Antoine Dechezleprêtre; Matthieu Glachant; Yann Ménière (Fondazione Eni Enrico Mattei (FEEM), 2007)
The Clean Development Mechanism (CDM) is expected to stimulate the North-South transfer of climate-friendly technologies. This paper provides an assessment of the technology transfers that take place through the CDM using a unique data set of 644 registered projects. It provides a detailed description of the transfers (frequency, type, by sector, by host country, etc.). It also includes an econometric analysis of their drivers. We show that transfer likeliness increases with the size of the projects. The transfer probability is 50% higher in projects implemented in a subsidiary of Annex 1 companies while the presence of an official credit buyer has a lower albeit positive impact. The analysis also yields interesting results on how technological capabilities of the host country influence technology diffusion in the CDM.
Keywords: Q5; Q55; 330; Kyoto Protocol; Clean Development Mechanism; International Technology Transfer; Internationale Umweltpolitik; Clean Development Mechanism; Technologietransfer; Wissenstransfer; Umweltökonomik